Destructive and non-destructive measurements of residual crop residue and phosphorus effects on growth and composition of herbaceous fallow species in the Sahel - Gerard, Bruno G.; Hiernaux, Pierre H.Y.; Muehlig-Versen, B.; Buerkert, Andreas (Springer, 2001)
Little is known about the residual effects of crop residue (CR) and phosphorus (P) application on the fallow vegetation following repeated cultivation of pearl millet [Pennisetum glaucum (L.) R. Br.] in the Sahel. The objective of this study, therefore, was (i) to measure residual effects of CR, mulched at annual rates of 0, 500, 1000 and 2000 kg CR ha 1, broadcast P at 0 and 13 kg P ha 1 and P placement at 0, 1, 3, 5 and 7 kg P ha 1 on the herbaceous dry matter (HDM) 2 years after the end of the experiment and (ii) to test a remote sensing method for the quantitative estimation of HDM. Compared with unmulched plots, a doubling of HDM was measured in plots that had received at least 500 kg CR ha 1. Previous broadcast P application led to HDM increases of 14% compared with unfertilised control plots, whereas no residual effects of P placement were detected. Crop residue and P treatments caused significant shifts in flora composition. Digital analysis of colour photographs taken of the fallow vegetation and the bare soil revealed that the number of normalised green band pixels averaged per plot was highly correlated with HDM (r = 0.86) and that red band pixels were related to differences in soil surface crusting. Given the traditional use of fallow vegetation as fodder, the results strongly suggest that for the integrated farming systems of the West African Sahel, residual effects of soil amendments on the fallow vegetation should be included in any comprehensive analysis of treatment effects on the agro-pastoral system.